2008
DOI: 10.1051/parasite/2008152105
|View full text |Cite
|
Sign up to set email alerts
|

New species of haematozoa from the avian families Campephagidae and Apodidae

Abstract: Summary :Leucocytozoon coracinae sp. nov. is described from the avian family Campephagidae and Hepatozoon apodis sp. nov. from the Apodidae. The distribution of these parasites within their respective families is discussed. Résumé : NOUVELLES ESPÈCES D'HAEMATOZOAIRES DES FAMILLES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In the past, the description of new haemoparasite species was often done using the limited information about vertebrate host specificity and the morphological features of blood stages [12][13][14][15][16][17]45]. When prominent data of molecular genetics appeared, the validity of many species names was questioned, new parasites were described, and old parasites were redescribed [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, the description of new haemoparasite species was often done using the limited information about vertebrate host specificity and the morphological features of blood stages [12][13][14][15][16][17]45]. When prominent data of molecular genetics appeared, the validity of many species names was questioned, new parasites were described, and old parasites were redescribed [1].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown the presence of Hepatozoon parasites in birds using exclusively morphological features of blood stages [ 12 , 13 , 15 , 16 , 17 , 18 ]. For instance, Merino et al [ 19 ] used DNA sequence information and proved the presence of Hepatozoon peircei in storm petrels Oceanodroma leucorhoa and Oceanodroma melania , both marine bird species belonging to the Procellariiformes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of Cape Verde, Hille et al [22] investigated the blood parasite prevalence in common kestrels using blood smears. During the last years, three studies have identified molecularly the prevalence and diversity of blood parasite lineages infecting wild birds from Madagascar [2325], adding valuable information to the previous knowledge based on blood smears [26, 27]. Although combining the identification of blood parasites based on the screening of blood smears and molecular approaches could add valuable information [7], molecular methods are broadly used as they allow the identification of genetic diversity and host-range of blood parasites [4, 8, 9, 14, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Either blood samples were examined microscopically [11, 12] or just a small number was analyzed by PCR [13]. So far, data about vectors in Madagascar transmitting avian malaria parasites are lacking.…”
Section: Introductionmentioning
confidence: 99%